Variance analysis as a tool of controlling food and beverage costs at Masmara Resort Canggu - Dewi, Ni Ketut Motik Diah Amara; Karmana, I Wayan; Jaya, I Made Sura Ambara (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
This research focuses on controlling food and beverage costs at Masmara Resort Canggu due to adverse variances between standard costs and actual costs. This study aims to determine the variance between standard costs and actual costs and the causes of variance and how to control food and beverage costs. This type of research is mixed method study, which is a sequential mixed methods strategy was used, especially a sequential exploratory strategy. The data sources used are primary data in the form of interview and observation results and secondary data in the form of standard recipes, reconciliation reports, sales reports, standard cost reports and actual cost reports. The data analysis techniques used are quantitative analysis techniques and control techniques. The results showed an unfavourable variance both in terms of the quantity of raw material use and also the price of raw materials caused by differences in the use of raw material quantities and differences in standard raw material prices with the actual. For food and beverage cost control, there are still discrepancies when purchasing goods above the standard price, receiving goods is carried out by unauthorized staff, storage does not match the type and does not apply the FIFO (First In First Out) system, and the production section does not use the standard recipe that has been set.